An Analysis of Factors That Influences Cottage Industry Development - Pathmananathan, P. Ravindran; Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2021)
Cottage Industry in Malaysia contributes key economic revenues for the village population. It is mainly small-scaled operations, using local resources and traditional skills with very low investments but fast returns. However, the industry may not be flourishing currently due to the lack of modern technology, facilities and knowledge transfer in place. Aim of this study is to determine the CI's current positions, challenges, and gaps in the state of Perak. This study was carried out via a self-administered structured questionnaire that equally distributed throughout the Perak State (North Perak, Central Perak and South Perak) involving 300 respondents. The study shows that a community's socioeconomic development and CI sector are influenced by a variety of factors. It is due to both internal and external causes, such as interest and self-motivation, as well as the positions of different organisations, as well as family and community support.